Outcomes of Expandable Interbody Devices in Lumbar Fusion: A Systematic Review and Meta-analysis. Issue 6 (July 2020) - Jenkins, Nathaniel W.; Parrish, James M.; Khechen, Benjamin; Block, Andrew M.; Lalehzarian, Simon P.; Brundage, Thomas; Hrynewycz, Nadia; Iyer, Sravisht; Singh, Kern
Abstract : Study Design: This was a systematic review. Objective: The objective of this study was to review radiographic, clinical, and surgical outcomes of expandable interbody device implantation following lumbar fusion. Summary of Background Data: Few studies have evaluated postsurgical outcomes of expandable implants following lumbar interbody fusion. Methods: A systematic review was performed to identify studies investigating expandable intervertebral body devices in lumbar fusion. Radiographic parameters, fusion assessments, patient-reported outcomes (PROs), complications, and revision data were recorded. A comparison of expandable and static devices was performed using a meta-analysis. Results: Eleven articles were included. Postoperative improvements for each radiographic parameters for expandable versus static device implantation ranged from: lumbar lordosis, +2.0 to +5.0 degrees (expandable) versus +1.0 to +4.4 degrees (static); segmental lordosis, +1.0 to +5.2 degrees (expandable) versus+1.1 to +2.3 degrees (static); disk height, +0.82 to +4.8 mm (expandable) versus +0.26 to +6.9 mm (static); foraminal height, +0.13 to +2.8 mm (expandable) versus and +0.05 to +3.0 mm (static). Fusion rates ranged from 72.1% at 6 months to 100% at terminal follow-up. Preoperative to final follow-up improvement for the various PROs assessed were: Oswestry Disability Index, −15.4 to −56.3 (expandable) versus −13.6 to −26.3 (static); Visual Analog Scale (VAS) Back, −3.2 to −6.0 (expandable) versus −3.1 to −4.1 (static); and VAS Leg, −2.9 to −7.1 (expandable) −3.0 versus −4.8 (static). Static cages had a reported complication rate ranging from 6.0% to 16.1% and a subsidence rate of 6.0%. Expandable cages had a reported complication rate that ranged from 0.0.% to 10.0% and a subsidence rate of 5.5%–10.0%. A meta-analysis demonstrated a statistically significant difference in the PRO Oswestry Disability Index, but not VAS Back, VAS Leg, or radiographic outcomes (disk height or foraminal height). Conclusion: There is no clear evidence for the use of expandable interbody devices over static devices.